2023
DOI: 10.1159/000530084
|View full text |Cite
|
Sign up to set email alerts
|

Population Pharmacokinetic Modeling to Inform Sertraline Dosing Optimization in Patients with Depression

Abstract: Sertraline is one of the most prescribed antidepressants, but its pharmacokinetic (PK) properties are still not completely characterized. Using nonlinear mixed-effects modeling, we examined factors influencing sertraline PK variability in outpatients with major depressive disorder. Blood samples from 53 male and female adults treated with sertraline orally were collected at a steady state. Various demographic and clinical covariates were tested by stepwise regression procedure. We found that sertraline clearan… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 24 publications
0
1
0
Order By: Relevance
“…Based on our study of sertraline, we found that the mean dose-adjusted serum drug concentration (concentration/daily dose) was consistent with the AGNP guidelines, suggesting that pharmacokinetic differences between races are minimal. In a PPK study of sertraline, sertraline concentration data from 53 patients were used to find that N-desmethyl sertraline was a covariate affecting sertraline clearance [ 25 ]. In another, PPK study on sertraline and escitalopram, the CYP2C19 genotype was found to be a potential factor affecting sertraline clearance [ 26 ].…”
Section: Discussionmentioning
confidence: 99%
“…Based on our study of sertraline, we found that the mean dose-adjusted serum drug concentration (concentration/daily dose) was consistent with the AGNP guidelines, suggesting that pharmacokinetic differences between races are minimal. In a PPK study of sertraline, sertraline concentration data from 53 patients were used to find that N-desmethyl sertraline was a covariate affecting sertraline clearance [ 25 ]. In another, PPK study on sertraline and escitalopram, the CYP2C19 genotype was found to be a potential factor affecting sertraline clearance [ 26 ].…”
Section: Discussionmentioning
confidence: 99%